2011
DOI: 10.1142/s0219635211002762
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuits of the Cerebellum: Hypothesis for Function

Abstract: The rapid growth of cerebellar research is going to clarify several aspects of cellular and circuit physiology. However, the concepts about cerebellar mechanisms of function are still largely related to clinical observations and to models elaborated before the last discoveries appeared. In this paper, the major issues are revisited, suggesting that previous concepts can now be refined and modified. The cerebellum is fundamentally involved in timing and in controlling the ordered and precise execution of motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 185 publications
(300 reference statements)
0
38
0
2
Order By: Relevance
“…There is increasing evidence that the time delays required to create opposing signals might be generated by the mossy fiber-granule cell circuitry in the mammalian cerebellum. Long term plasticity at the mossy fiber—granule cell synapse can delay incoming signals for up to 100 ms, or even longer when larger sections of the circuitry are entrained (D'Angelo, 2011). Similar delays are generated in cerebellar-like structures involving the mossy fibers, granule cells and unipolar brush cells (Kennedy et al, 2014).…”
Section: Cerebellum and Motor Domainmentioning
confidence: 99%
“…There is increasing evidence that the time delays required to create opposing signals might be generated by the mossy fiber-granule cell circuitry in the mammalian cerebellum. Long term plasticity at the mossy fiber—granule cell synapse can delay incoming signals for up to 100 ms, or even longer when larger sections of the circuitry are entrained (D'Angelo, 2011). Similar delays are generated in cerebellar-like structures involving the mossy fibers, granule cells and unipolar brush cells (Kennedy et al, 2014).…”
Section: Cerebellum and Motor Domainmentioning
confidence: 99%
“…Although this mechanism supports the core process of error-correction in the motor learning theory and subsequent derivations, this same mechanism alone can only account for limited aspects of biological learning. A new spectrum of possibilities was opened by the discovery on multiple forms of synaptic plasticity (Hansel et al, 2001; Evans, 2007; Ohtsuki et al, 2009; D'Angelo, 2011; Gao et al, 2012). A recent model has shown that plasticity at deep-cerebellar nuclei (DCN) synapses can indeed account for learning on multiple time scales and for generalization (Garrido et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cerebellum is critical for revealing differences between predictions elaborated by the cortex and the stimuli conveyed by the senses. Thus, dysfunction of the cortico-cerebellar circuits may affect the detection of novelty and impair attention switching (D’Angelo, 2011). These complex functions (sensory prediction and novelty detection) seem to be impaired in BPD patients and are widely described by clinicians.…”
Section: Discussionmentioning
confidence: 99%